Questioning the Re-functioned Monastery Buildings in Northern Cyprus - Mısırlısoy, Damla; Günçe, Ka?an (Springer Nature, 2022)
Cyprus, which has a rich cultural background, is an island where many ethnic groups have lived. In order to understand the cultures of different ethnic groups that existed on the island, architectural heritage should be observed. In 1974, the island is divided into two as north and south. The Turkish Cypriots started living in the north, and the Greek Cypriots began to live in the south. A large number of cultural heritage buildings were abandoned since their communities migrated. Since they lost their communities, many of the religious buildings have not been used for a long time. As a result, the mosques in the south, the churches and monasteries in the north were left abandoned without taking precautions. In 2003, communities had the chance to visit their places of worship after the opening of checkpoints. Some of these structures, which cannot be used by the community, have been demolished and abandoned without any use. Since the reuse of religious heritage is a sensitive issue, many religious heritage buildings still exist abandoned and they need to be reused by re-thinking the different dimensions of the issue. Within the scope of the study, monastery buildings that are located in the northern part of the island and lost their ethnic community are discussed. The aim of the study is to question the condition of these structures before 1974, between 1974 and 2004 and after 2004 in the light of political conflicts and propose conservation and reuse strategies for these monasteries in order to keep the cultural memory alive. The method of the study is based on literature survey, observations through site surveys and interviews. Spiritual value of the monastery buildings is the most important heritage value that should be taken into consideration in the decision of the new use. Monasteries should be reused to contribute to religious tourism. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
5th International Conference on Conservation of Architectural Heritage, CAH 2021 -- 2021-02-08 through 2021-02-10 -- Virtual, Online -- 277349
Keywords: Adaptive reuse; Conflict; Cyprus; Ethnic beliefs; Monastery; Religious heritage